2021
DOI: 10.1038/s41598-021-97436-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute carbon monoxide poisoning with low saturation of carboxyhaemoglobin: a forensic retrospective study in Shanghai, China

Abstract: Carbon monoxide (CO) poisoning is a common cause of death, leading to morbidity and mortality worldwide. Features of the CO poisoning with low carboxyhemoglobin (COHb) levels remain to be characterized. This study collected a total of 307 CO poisoning cases from Shanghai Public Security Bureau, an official organization that handles the most complicated and life-threatening cases across Shanghai municipality in China, and regrouped these cases into three categories: group 1, 10% < COHb% < 30% (n = 58); gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…The acute CO poisoning was associated with the temperature in Taiwan, where an RR-0.0973 value is less than one, indicating less environmental impact [32]. In the current study, the calculated value of RR was 1.44 for CO poisoning as mentioned in Table 2, which could have severe effects on the health of respondents of steel industries at Hattar.…”
Section: Discussionmentioning
confidence: 56%
“…The acute CO poisoning was associated with the temperature in Taiwan, where an RR-0.0973 value is less than one, indicating less environmental impact [32]. In the current study, the calculated value of RR was 1.44 for CO poisoning as mentioned in Table 2, which could have severe effects on the health of respondents of steel industries at Hattar.…”
Section: Discussionmentioning
confidence: 56%
“…The most common symptoms of CO poisoning include nausea, headache, dyspnea and tachycardia. If it is not detected and treated in time, the symptoms will worsen and neurological symptoms, such as hallucinations, dizziness, confusion, seizures, and at a maximum extent to respiratory arrest [10]. When the patient is in a coma, the body may be in direct contact with burning coal or a high-temperature furnace.…”
Section: Discussionmentioning
confidence: 99%
“…This also suggests that COHb level alone cannot be used to judge the severity of poisoning. A forensic study on low COHb levels of carbon monoxide poisoning in Shanghai, China 12 showed that acute carbon monoxide poisoning with low COHb (less than 30%) still resulted in patient death, accounting for 18.9% (58/307) of the total cases studied. A retrospective study conducted by the Portuguese National Institute of Legal Medicine and Forensic Science showed that there was one case of blood and internal organs with cherry red color, but the detected COHb level was only 3% 13 .…”
Section: Cohb Levelmentioning
confidence: 99%